Distribution, speciation, bioavailability, risk assessment, and limit standards of heavy metals in Chinese herbal medicines - Tian-Tian Zuo; Yao-Lei Li; Ying Wang; Yuan-Sheng Guo; Ming-Rui Shen; Jian-Dong Yu; Jing Li; Hong-Yu Jin; Feng Wei; Shuang-Cheng Ma (Elsevier, 2023)
Introduction: There are increasing concerns on the safety of traditional Chinese medicine (TCM) worldwide. Chinese herbal medicine (CHM), an important type of TCM, may be contaminated by exogenous harmful substances, including heavy metals during planting, collecting, and processing. The consumption of CHM polluted with heavy metals may lead to a serious hazard to users. Though effective strategies to minimize the risks related to heavy metals is challenging, it is of great significance for optimizing health. Result: This review deals with the characteristics of heavy metals in Chinese herbal medicine (CHM), in terms of heavy metal distribution, speciation, bioavailability, detection methods, risk assessment and limit standards. Especially, the development process of the consistent limit guidance values of heavy metals in CHM in Chinese Pharmacopoeia (2020 edition) were discussed. Finally, strategies to limit the health implications of heavy metal in CHM were highlighted, involving strictly controlling the pollution of heavy metals in CHM, encouraging the innovation of speciation and bioavailability techniques, and formulating international guideline and standards for heavy metals in CHM. Conclusion: All in all, this review will help researchers to explore fresh methodologies to the issue of heavy metals in CHM, thereby proposing approaches towards safe use of TCM in the clinic and promoting the sustainable and healthy development of TCM industry.